Reliability of Collector (Bottle) Set in ACS (Texas Journal of Multidisciplinary Studies, 2022)
DC motors are widely used in industry due to their deep, smooth and economical speed control. However, the reliability of DC machines is lower than that of asynchronous machines due to the presence of a sliding contact collector-brush combination. Statistical analysis shows that in terms of reliability in AC machines, it is necessary to distinguish four "weak sets": collector-brush set, bearing ring, armature ring, drive throwing pot we pay attention to the collector-brush set, taking into account the above.